2022
DOI: 10.1111/bjh.18517
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the variability of the human leukocyte antigen peptide‐binding pockets in patients with acute leukaemia

Abstract: Summary The association between acute lymphoblastic leukaemia (ALL) and acute myeloid leukaemia (AML) and the human leukocyte antigens (HLA) has rarely been studied in terms of diversity of peptide‐binding pockets. The objective of this study was to analyse whether motifs of HLA class I and class II peptide‐binding pockets and/or their amino acid positions were differentially associated with ALL and AML. We included 849 patients from the Eurocord/European Blood and Marrow Transplant registry. The HLA peptide‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Importantly, only motifs belonging to class II HLA (DQB1, DRB1) pockets were characteristically associated with ALL in this study 6 . Analogies to previous reports on specific class II HLA alleles and human pathology of an autoimmune nature and cancer are obvious and warrant further studies.…”
Section: Editorialsupporting
confidence: 75%
See 2 more Smart Citations
“…Importantly, only motifs belonging to class II HLA (DQB1, DRB1) pockets were characteristically associated with ALL in this study 6 . Analogies to previous reports on specific class II HLA alleles and human pathology of an autoimmune nature and cancer are obvious and warrant further studies.…”
Section: Editorialsupporting
confidence: 75%
“…Importantly, only motifs belonging to class II HLA (DQB1, DRB1) pockets were characteristically associated with ALL in this study. 6 Analogies to previous reports on specific class II HLA alleles and human pathology of an autoimmune nature and cancer are obvious and warrant further studies. A recent work on HLA evolutionary divergence (HED), a new metric that can be considered as an indirect measure of the breadth of the human immunopeptidome, found that lower class II HED imprinted a higher risk of leukaemic progression in patients with acquired aplastic anaemia.…”
Section: Editorialmentioning
confidence: 62%
See 1 more Smart Citation
“…13 Some studies have demonstrated the implication of specific positions and/or pockets within peptide-binding regions in the risk to develop immune-related disorders, as these pockets within certain HLA molecules possess a pivotal role in the selection and stability of antigenic peptides. 14,15 We deciphered the HLA peptide-binding diversity in acute myeloid leukaemia (AML) and acute lymphoblastic leukaemia (ALL), demonstrating the relationship between specific HLA class II motifs in ALL, but not in AML, and suggesting an HLA-mediated differential risk for both types of leukaemia. 15 Therefore, the objective of this study was to analyse whether HLA amino acid pockets constituting the peptide-binding grooves of HLA class I HLA-A, -B and -C (B and F pockets) and HLA class II -DRB1 (P4, P6 and P9) and -DQB1 (P4 and P9) were associated with post-UCBT outcomes in patients with acute leukaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Within the HLA class II molecules, five pockets (P1, P4, P6, P7 and P9) govern peptide management 13 . Some studies have demonstrated the implication of specific positions and/or pockets within peptide‐binding regions in the risk to develop immune‐related disorders, as these pockets within certain HLA molecules possess a pivotal role in the selection and stability of antigenic peptides 14,15 …”
Section: Introductionmentioning
confidence: 99%